(untitled) (Global Journal of Science Frontier Research, 2017)
The objective of this work was to assess the genetic parameters in Coffea Robusta clones using mixed model. The experiments were carried out during four years, in complete block design, and one plant per plot, at Oratorio of Minas Gerais state, Brazil. The clones were evaluated for vigor, reaction to rust, reaction to cercospera, number of or to tropicos branches, number of plegiotropics branches, plant height, diameter of stem, fruit maturity, diameter of canopy, fruit size and production of fruits. The data were analyzed using the mixed model methodology (REML/BLUP) of Selegen software for estimation of genetic parameters in C.canephora breeding. The results showed a low genetic variability among the clones of Robusta for all the evaluated traits. On the other hand, relatively high residual coefficient of variation for most of the traits was recorded implying that these traits seem to be highly influenced by the environmental variation.